1995
DOI: 10.1074/jbc.270.13.7025
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Soluble Trimeric CD40 Ligand Is Biologically Active

Abstract: CD40 ligand (CD40L) is expressed on the surface of activated CD4+ T cells, basophils, and mast cells. Binding of C40L to its receptor, CD40, on the surface of B cells stimulates B cell proliferation, adhesion and differentiation. A preparation of soluble, recombinant CD40L (Tyr-45 to Leu-261), containing the full-length 29-kDa protein and two smaller fragments of 18 and 14 kDa, has been shown to induce differentiation of B cells derived either from normal donors or from patients with X-linked hyper-IgM syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
113
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(118 citation statements)
references
References 23 publications
3
113
0
2
Order By: Relevance
“…Truncated, soluble derivatives of this molecule are secreted/shed from activated cells, and retain the ability to bind and activate CD40, which is a 45-to 50-kDa type I integral membrane glycoprotein and a member of the TNFR superfamily (21,22). Cells known to express CD40 include B cells, dendritic cells, endothelial cells, and macrophages, as well as astrocytes and microglia (23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Truncated, soluble derivatives of this molecule are secreted/shed from activated cells, and retain the ability to bind and activate CD40, which is a 45-to 50-kDa type I integral membrane glycoprotein and a member of the TNFR superfamily (21,22). Cells known to express CD40 include B cells, dendritic cells, endothelial cells, and macrophages, as well as astrocytes and microglia (23)(24)(25)(26).…”
mentioning
confidence: 99%
“…The binding of CD40L to its receptor, CD40, on the surfaces of B cells stimulates B-cell proliferation, adhesion, and differentiation. A soluble isoform of CD40L has been shown to exist in the circulation, exhibiting full activity in B-cell proliferation and differentiation assays (16). It was reported that the treatment of wild-type CD40 mice with sCD40L fusion protein elicited a pulmonary inflammatory response that was not observed in identically treated CD40 knockout mice (21).…”
mentioning
confidence: 99%
“…Although sCD40L released from activated helper T cells apparently forms homotrimers, lyophilized recombinant human CD40L protein forms primarily monomers, exhibiting only faint biological activity to stimulate CD40-positive cells, such as DC and leukemic B cells. [26][27][28] To overcome the insufficient function of sCD40L to stimulate DC, we investigated whether adenovirus-mediated transduction of the human CD40L gene to DC (CD40L-DC) is efficient approach for the induction of Twenty-four hours after cocultivation, NK cells were washed and replated at a cell density of 2 3 10 5 cells/ml. After 48 hr, the IFNg concentration in culture supernatants was quantified by ELISA.…”
Section: Discussionmentioning
confidence: 99%